2013
DOI: 10.4103/0250-474x.117398
|View full text |Cite
|
Sign up to set email alerts
|

Determination of trace metals, moisture, pH and assessment of potential toxicity of selected smokeless tobacco products

Abstract: The characterization and classification of smokeless tobacco products has been a continuously evolving process. This is based on a number of different parameters like nicotine content, moisture content, amount of heavy metals, pH, and in vitro cytotoxicity assays. Their contexts often vary between countries, research institutions, and legal requirements. The categorisation of these products is quite challenging due to the diffused sample sizes, diverse array of branded products on offer, and the absence of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…E-cigarettes are devices that include a battery-powered heating element designed to heat and aerosolize liquids containing varying levels of nicotine, flavoring agents, a number of unknown components, and in some cases tobacco itself. 1 Aerosolized nicotine in e-cigarettes contains glycerine to mimic smoke of conventional cigarettes while supposedly delivering lower toxin levels than those found in a conventional cigarette. 2–5 Vaporizers (or vape-pens) are similar to e-cigarettes, but typically contain a larger battery with variable heat settings to heat a refillable tank with a wick for liquid nicotine or a compartment for vaporizing THC oil or even cannabis buds.…”
mentioning
confidence: 99%
“…E-cigarettes are devices that include a battery-powered heating element designed to heat and aerosolize liquids containing varying levels of nicotine, flavoring agents, a number of unknown components, and in some cases tobacco itself. 1 Aerosolized nicotine in e-cigarettes contains glycerine to mimic smoke of conventional cigarettes while supposedly delivering lower toxin levels than those found in a conventional cigarette. 2–5 Vaporizers (or vape-pens) are similar to e-cigarettes, but typically contain a larger battery with variable heat settings to heat a refillable tank with a wick for liquid nicotine or a compartment for vaporizing THC oil or even cannabis buds.…”
mentioning
confidence: 99%
“…Substances such as slaked lime are often added to the tobacco blend during the curing process, thereby increasing the alkaline pH. 7 The Afzal samples in this study had a higher pH value (pH 10.46) than the value described in the quality standards used by GOTHIATEK ® (Swedish Match, Stockholm, Sweden)…”
Section: Discussionmentioning
confidence: 78%
“…7,19 Higher nicotine levels are found in moist snuff in comparison to the dry form. 1 Additionally, it has been found that American moist snuff contains higher levels of NO 2 -and Cl -than the dry type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CPF is based on the daily dose rate in mg/kg-bodyweight/day to induce tumors in half of test animals that would have remained tumor-free at zero dose. For the purposes of this study, it was arbitrarily assumed that 10 grams dry weight product per day was consumed by a 70 kg adult STPs user over a 30 year period during a 70-year lifetime (Ayo-Yusuf and Connolly, 2011; Prabhakar et al, 2013; Zakiullah et al, 2012). The equation used was: incremental lifetime cancer risk=ADE lifetime × CPF (where ADE lifetime =lifetime average daily oral exposure (mg/kg bodyweight/day) and CPF=carcinogenic potency factor ((mg/kg bodyweight/day) −1 )).…”
Section: Methodsmentioning
confidence: 99%